Effect Of Financial Technology On Cash Holding In Indonesia Using Autoregressive Distributed Lag (ARDL) - Diputra, Sachio Senna; Zen, Tuntun Salamatun; Hasanah, Eneng Nur (Integrasi Sains Media, 2023)
The rapid proliferation of financial technology (Fintech) has revolutionized the landscape of financial services globally, presenting digital alternatives to conventional banking and payment methods. Indonesia has emerged as a noteworthy adopter of Fintech, driven by the widespread usage of smartphones and government initiatives to foster financial inclusion. Nonetheless, the empirical research concerning the association between Fintech adoption and cash-holding behaviour in Indonesia remains limited. This study explores Fintech's influence on individuals' cash holding patterns in the country, considering direct indicators such as debit cards, credit cards, electronic money, mobile banking, and internet banking. A time-series analysis covering the period from M5 2013 to M3 2023, based on secondary data from the Bank Indonesia Statistic Database, is employed to achieve this research objective. The analytical framework utilizes the Autoregressive Distributed Lag (ARDL) bounds testing approach, accounting for the explanatory variables' concurrent and lagged effects. The empirical findings reveal a significant positive relationship between debit cards, mobile banking, and internet banking usage in short-term cash-holding behaviour. In contrast, credit card usage exhibits a negative and statistically significant association with long-term cash holding. These results contribute to a comprehensive understanding of how Fintech adoption shapes cash-holding behaviour in Indonesia and provide valuable insights into the country's transition toward a cashless society.